Mediation Role of Perceived Benefit in the Relationship between Perceived Government Support, Religiosity, Awareness and the Acceptance of Islamic Microfinancing in Nigeria - Mas’ud, Abdulsalam; Shittu, Isah; Umar, Umar Bello (European Journal of Islamic Finance, 2020)
Social Exchange Theory highlights the possible mediating role perceived benefit in social and economic relationships, however, extent literature falls short is validating such theoretical insights in the context of Islamic microfinance. Following this theoretical insights the mediating role of perceived benefit on the relationship between perceived government support, religiosity, awareness and intention to accept Islamic micro-financing was examined. Quantitative research design through data collected from smallholder farmers in Jigawa state was employed; the data was analyzed using PLS-SEM. The finding revealed that perceived benefit mediates the relationship between perceived government support, religiosity, awareness and intention to accept Islamic micro-financing. It implied that perceiving the benefit is one of the mechanisms through which government support, religiosity and awareness influence intention to accept Islamic micro-financing. The study expands the understanding of TPB through the support of SET to explain the mediating effects of perceived benefits in the context of Islamic micro-financing. Thus, it will benefit policymakers in understanding that perceived benefit of Islamic micro-financing is a key to its acceptance, hence, the need for awareness campaigns, support services and religious preaching to that end. Implementing the finding will not only solve problem of access to finance among the smallholder farmers but also ease life through employment generation and poverty eradication. To the researchers’ knowledge, this work could be first to examine the mediating role of perceived benefit in the context of Islamic microfinance among the smallholder farmers with inferences from Social Exchange Theory